A stable and practical nickel catalyst for the hydrogenolysis of C–O bonds. Issue 1 (5th December 2016) - Cui, Xinjiang; Yuan, Hangkong; Junge, Kathrin; Topf, Christoph; Beller, Matthias; Shi, Feng
Abstract : The selective hydrogenolysis of C–O bonds constitutes a key step for the valorization of biomass including lignin fragments. Abstract : The selective hydrogenolysis of C–O bonds constitutes a key step for the valorization of biomass including lignin fragments. Moreover, this defunctionalization process offers the possibility of producing interesting organic building blocks in a straightforward manner from oxygenated compounds. Herein, we demonstrate the reductive hydrogenolysis of a wide variety of ethers including diaryl, aryl–alkyl and aryl–benzyl derivatives catalyzed by a stable heterogeneous NiAlO x catalyst in the presence of a Lewis acid (LA). The special feature of this catalyst system is the formation of substituted cyclohexanols from the corresponding aryl ether.